Extreme Temperature Events in Kazakhstan and Their Impacts on Public Health and Energy Demand - Parya Broomandi; Alfrendo Satyanaga; Mehdi Bagheri; Mostafa Hadei; David Galán‐Madruga; Ali Mozhdehi Fard; Adib Roshani; Aram Fathian; Amir Nourian; Michael Leuchner; Klaus Reicherter; Mehdi Hamidi; et al. (Global Challenges)
Abstract Extreme temperature events such as heatwaves are becoming increasingly severe and frequent because of climate change, posing significant challenges to public health and energy infrastructure. This study explores the impacts of extreme temperature events leading to heat‐/cold waves on public health and energy consumption in Kazakhstan from 1959 to 2021. The most striking trends in heatwave‐related indices emerge in the western and southwestern regions. Conversely, despite heightened coldwave intensity, a decline is noted in their frequency and number. The impact of heatwaves on various health conditions, notably consistent and statistically significant rises in all‐cause and cardiovascular mortalities, is observed. Shifts in energy demand are also unveiled with a noticeable spike in cooling‐degree days and a reduction in heating‐degree days. The mean total energy consumption stood at 552 kWh across the country with an average annual energy generation of ≈8.76 kWh. To gauge the environmental implications, the mean CO2 emissions are estimated at 464 kg per kWh for both heating and cooling purposes. With climate change set to escalate heatwaves, the need for comprehensive health planning is underscored to mitigate their adverse health impacts. Furthermore, transitioning from fossil fuels to green energy sources is crucial to reduce the environmental footprint.